2014
DOI: 10.1111/tbed.12250
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Potential of Two Previously Uncharacterized African Swine Fever Virus Isolates from Southern Africa and Heterologous Cross Protection of an Avirulent European Isolate

Abstract: Summary African swine fever (ASF) is a mostly fatal viral infection of domestic pigs for which there is no vaccine available. The disease is endemic to most of sub‐Saharan Africa, causes severe losses and threatens food security in large parts of the continent. Naturally occurring attenuated ASF viruses have been tested as vaccine candidates, but protection was variable depending on the challenge virus. In this study, the virulence of two African isolates, one from a tick vector and the other from an indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Low virulence isolates may cause few if any deaths and a chronic form of disease characterized by the absence of vascular lesions but signs such as delayed growth, emaciation, joint swelling, skin ulcers and lesions associated with secondary bacterial infection. Moderately virulent and low virulence isolates were described after the introduction of the virus into Spain and Portugal, and similar isolates have now been described from different countries in Africa (Souto et al, 2016) and also in Eastern Europe (Gallardo et al, 2018; Zani et al, 2018). Detection of ASFV specific antibodies in serum from wild boar in Eastern Europe may indicate reduced virulence of circulating isolates, since in acute infections animals die before an antibody response is detected.…”
Section: Infection and Pathogenesis In Different Host Speciesmentioning
confidence: 55%
“…Low virulence isolates may cause few if any deaths and a chronic form of disease characterized by the absence of vascular lesions but signs such as delayed growth, emaciation, joint swelling, skin ulcers and lesions associated with secondary bacterial infection. Moderately virulent and low virulence isolates were described after the introduction of the virus into Spain and Portugal, and similar isolates have now been described from different countries in Africa (Souto et al, 2016) and also in Eastern Europe (Gallardo et al, 2018; Zani et al, 2018). Detection of ASFV specific antibodies in serum from wild boar in Eastern Europe may indicate reduced virulence of circulating isolates, since in acute infections animals die before an antibody response is detected.…”
Section: Infection and Pathogenesis In Different Host Speciesmentioning
confidence: 55%
“…Work performed decades ago clearly demonstrated that experimental vaccines based on physical or chemical inactivated ASFV failed to induce solid protective immunity ( 15 17 ), an observation that has been confirmed using more modern adjuvants ( 18 ). Conversely, live attenuated ASFV isolates, either naturally isolated or obtained by tissue culture adaptation, have been demonstrated to confer solid protection against experimental infections with homologous virulent viruses ( 19 , 20 ) and only in a limited manner against heterologous ASFV challenges ( 21 23 ). Safety concerns have thus far hampered their field implementation, but live attenuated viruses (LAVs) have become essential tools to better understand the role that both specific antibodies and T cells play in ASF protection.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ASF in Eastern and Southern Africa historically focused strongly on the sylvatic cycle and on the biological characteristics of the virus (De Kock et al, ; DeTray, ; Montgomery, ; Peirce, ; Plowright & Parker, ; Plowright, Parker, & Peirce, , ; Plowright et al, ; Plowright, Perry, & Peirce, ; Plowright, Perry, Peirce, & Parker, ; Thomson, ; Thomson et al, ). Recent research has continued to focus on both these aspects, using molecular genetic technology to further clarify the epidemiology and also to contribute to improved diagnostic tests and the continuing efforts to develop a vaccine (Bastos, Penrith, Macome, Pinto, & Thomson, ; Bishop et al, ; Boshoff, Bastos, Gerber, & Vosloo, ; Burrage, ; de Villiers et al, ; Lubisi et al, ; Lubisi, Bastos, Dwarka, & Vosloo, ; Mulumba‐Mfumu, Goatley, Saegerman, Takamatsu, & Dixon, ; Phologane et al, ; Quembo et al, , ; Simulundu et al, ; Simulundu et al, ; Souto et al, ). Molecular genetic information at least at p72 genotype level is available for most ECSA countries (Figure ).…”
Section: Knowledge Gaps and The Way Forwardmentioning
confidence: 99%
“…Although ASF in Africa usually manifests as an acute severe disease, viruses of varying virulence occur naturally in Africa. Field strains of low to moderate virulence include a non‐haemadsorbing virus from an outbreak in DRC (Thomson, Gainaru, & Van Dellen, ), an outbreak virus in Angola (Nsalambi, ) and a moderately virulent tick isolate from South Africa (Souto et al, ). Since a level of resistance to the pathogenic effects of ASF exists in domestic pigs in several endemic areas in ECSA, virus‐based studies will be necessary to determine or confirm variations in virulence.…”
Section: Knowledge Gaps and The Way Forwardmentioning
confidence: 99%